West Indian Fruit Fly, Anastrepha obliqua (Macquart) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; John B. Heppner; Gary J. Steck; Thomas R. Fasulo (EDIS)
The West Indian fruit fly, Anastrepha obliqua (Macquart), occurs throughout the Caribbean, south to southern Brazil. It is the most abundant species of Anastrepha in the West Indies and one of the most abundant species in Panama. A. obliqua is a major pest of mangoes in most tropical countries, making the production of some varieties unprofitable. Some varieties, however, are little damaged. It, like the Caribbean fruit fly, A. suspensa (Loew), also attacks other tropical fruits of little economic importance. A. obliqua has also been called the Antillean fruit fly. This document is EENY-198 (originally published as DPI Entomology Circulars 101 and 339), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2001.